1971
DOI: 10.1210/jcem-33-3-409
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Intravenous Glucose Loads, Insulin Responses and Glucose Disappearance Rate1

Abstract: In order to evaluate the relation between insulin responses, glucose loads and glucose disappearance rate, normal subjects were given glucose doses from 0.5 to 40 g by rapid intravenous injection. A highly linear correlation was seen between dose and the rapidly attained peak plasma glucose level measured as either the mean of the 3-through 5-min (3-5') absolute (r=+.98) or 3-5' incremental (A) (r=+.98) glucose value, suggesting any of these parameters can be employed as an index of the glucose stimulus. Estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
1

Year Published

1973
1973
2003
2003

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(51 citation statements)
references
References 14 publications
4
46
1
Order By: Relevance
“…the total 0-10 min area under the curve (0-10' area; mU-1 -I. min 1), 2. the incremental 0-10 rain area above fasting concentrations [4], (A 0-10' area; mU.1-1.min ~) 3. the sum of the 1 and 3 min concentrations [1], (1'+3' insulin; mU/1) 4. the mean of the incremental 3 to 5 min values above fasting concentrations [5], (A 3-5' insulin; mU/1).…”
Section: Discussionmentioning
confidence: 99%
“…the total 0-10 min area under the curve (0-10' area; mU-1 -I. min 1), 2. the incremental 0-10 rain area above fasting concentrations [4], (A 0-10' area; mU.1-1.min ~) 3. the sum of the 1 and 3 min concentrations [1], (1'+3' insulin; mU/1) 4. the mean of the incremental 3 to 5 min values above fasting concentrations [5], (A 3-5' insulin; mU/1).…”
Section: Discussionmentioning
confidence: 99%
“…The normal B-cells are most responsive in the region of the overnight fasting glucose concentration [17]; if there were a decreased number of B-cells those remaining would have to function towards their maximal capacity [18]. This would result in a decreased capacity to respond to changes in plasma glucose, which would affect both the basal and stimulated insulin secretion.…”
Section: Discussionmentioning
confidence: 99%
“…However , increased amounts of secreted IRI did not produce an increased action of insulin on BG level, glucose tolerance or glucose assimilation [10,40]. In man, a defective early phase IRI increase may indicate pre-diabetes [7,8]; and Lerner et al [25] showed some interaction between the early IRI increase and the glucose assimilation constants. Other authors found no correlation, or a contrary one, between such parameters in the peripheral blood [/, 30,39,40].…”
Section: Discussionmentioning
confidence: 99%